2a - 5b = 3 ...........(1)

3a + b = 4.................(2)

We will solve the system usin the substitution method.

From (2) we will rewrite:

3a + b = 4

==> b= 4 - 3a

Now we will subiute b value in (1):

2a-5b = 3

==> 2a - 5(4-3a)...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

2a - 5b = 3 ...........(1)

3a + b = 4.................(2)

We will solve the system usin the substitution method.

From (2) we will rewrite:

3a + b = 4

==> b= 4 - 3a

Now we will subiute b value in (1):

2a-5b = 3

==> 2a - 5(4-3a) = 3

=> 2a - 20 + 15a = 3

=> 17a = 23

**==> a= 23/17 **

Now to find b, we will substitute:

==> b= 4 - 3a

= 4 - 3(23/17)

= 4- 69/17

= (68-69)/17

= -1/17

**==> b= -1/17**